Wireless receiver design for digital communications - McClaning, Kevin 1959- (SciTech Publishing, 2012)
The book reviews developments in the following fields: wireless receiver design; digital communication; radio frequency basics; signal; noise; modulation; propagation; antenna; filter; mixer; oscillator; cascade design; and demodulation.